Environmental implications of animal wastes pollution on agricultural soil and water quality - Christopher O. AKINBILE; Andrew E. ERAZUA; Toju E. BABALOLA; Fidelis O. AJIBADE (Soil and Water Research, 2016)
An attempt was made to ascertain the environmental effects of animal wastes pollution on agricultural soil and water quality at the oldest teaching and research farm, Federal University of Technology, Akure, Nigeria. Physical, chemical, and bacteriological analyses of water (shallow well) and soil samples were carried out to determine the present quality status. Fifteen soil samples collected at the centre of the animal wastes dump and at a distance of 5 and 10 m, and three different samplings done on the water source were analyzed. The parameters determined using APHA standard procedures included: turbidity, temperature, pH, alkalinity, sulphide, phosphate, dissolved oxygen, total dissolved solids, total hardness, biochemical oxygen demand, total iron, nitrate, chloride, calcium, and heavy metals like copper, zinc, and lead. Most of the parameters indicated pollution including heavy metals presence with the exception of Pb, Zn, Mn, Cu, and Cr that were not detected in water samples. Concentrations of nitrate, biochemical oxygen demand, SO42-, PO43-, and Cl- were 0.20, 3.20, 10.50, 3.5, and 20.4 mg/l respectively, while those of detected heavy metals such as Mg and Ni were 1.98 and 10.03 mg/l, respectively. Soil water holding capacity, porosity, pH, organic matter, organic carbon, and organic nitrogen ranged from 33.34 ± 3.73 to 59.06 ± 5.69, 34.6 ± 3.28 to 52.43 ± 5.5, 6.56 ± 0.03 to 7.54 ± 0.03, 2.32 ± 0.03 to 5.35 ± 0.03, 1.33 ± 0.01 to 3.11 ± 0.01, and 0.58 ± 0.07 to 1.13 ± 0.03%, respectively. The results showed that the well is strongly polluted with bacteria and pathogens and requires considerable treatment before use while the soil is suitable for crop production.